2015
DOI: 10.1055/s-0040-1703880
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Communication Skills Between Undergraduate Dental Students With and Without Prior Training in Effective Communication

Abstract: Aim: In the present era of relationship-based care, effective communication between practitioners and patients vastly affects treatment planning and ultimately patient satisfaction.This study compared the communication skills of two groups of final year's undergraduate dental students with and without prior training in effective communication. Methodology: Eighty final year student were asked to participate in the study. Participants were randomly divided into two groups of forty each. One group rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A 360-degree review approach is reported to be superior to other traditional forms of evaluation and feedback as this method is known to initiate a vast positive change and provides a more efficient, thorough and accurate assessment of performance reviews. 8 In comparing all three perspectives, the highest mean score was given by patients while the lowest mean score was documented by the clinical instructor. Interaction between students and patients with short non-medical communication before the start of treatment may have built rapport among them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A 360-degree review approach is reported to be superior to other traditional forms of evaluation and feedback as this method is known to initiate a vast positive change and provides a more efficient, thorough and accurate assessment of performance reviews. 8 In comparing all three perspectives, the highest mean score was given by patients while the lowest mean score was documented by the clinical instructor. Interaction between students and patients with short non-medical communication before the start of treatment may have built rapport among them.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the stakeholders are patients and the supervisors are the clinical instructor. A 360‐degree review approach is reported to be superior to other traditional forms of evaluation and feedback as this method is known to initiate a vast positive change and provides a more efficient, thorough and accurate assessment of performance reviews 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CS can be taught through formal course activities or indirectly through modelling and mentorship by their instructors . In the literature, students have been rated as stronger communicators by patients and third party observers following communication skills learning (CSL) experiences. This suggests that optimising the CSL curriculum can support CS of future dentists.…”
Section: Introductionmentioning
confidence: 99%